1999
DOI: 10.1159/000016899
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Lessons Learned from 10 Years of Expandable Gastrointestinal Prostheses

Abstract: Initially inserted percutaneously for malignant biliary stenoses, expandable gastrointestinal prostheses have evolved as primary treatment for malignant dysphagia and as an alternative to plastic prostheses for some types of obstructive jaundice. They are also in their infancy as a means to palliate unresectable obstructions of the gastric outlet, small bowel, and colorectum. Despite a decade of development, problems persist and include: maldeployment; inadequate expansion; ingrowth; overgrowth; erosion, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Recurrent dysphagia being the leading symptom of stent dysfunction has been observed in this study and by others in as many as 50% of patients during a follow-up of 4-10 weeks [10,11]. Recanalization procedures such as laser therapy or further stent insertion, but also systemic chemotherapy and radiation seem to be of major importance to prolong stent patency [4,[6][7][8][9][10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Recurrent dysphagia being the leading symptom of stent dysfunction has been observed in this study and by others in as many as 50% of patients during a follow-up of 4-10 weeks [10,11]. Recanalization procedures such as laser therapy or further stent insertion, but also systemic chemotherapy and radiation seem to be of major importance to prolong stent patency [4,[6][7][8][9][10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 67%
“…However, favorable factors such as ease of placement, rapid relief of dysphagia, and improvement of quality of life should be weighed against delayed complications, including tumor in-or overgrowth, food bolus obstruction, development of fistulas, and stent migration [3][4][5][6][7]. Recurrent dysphagia being the leading symptom of stent dysfunction has been observed in this study and by others in as many as 50% of patients during a follow-up of 4-10 weeks [10,11].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Th e fi rst is stenting using rigid self-expandable metal stents (SEMSs). Despite early enthusiasm and a high immediate success rate, more recent studies including longer follow-up report important disadvantages and late complications with this treatment (dislocation, tumor overgrowth or ingrowth, and late fi stulization) ( 1,2 ). Moreover, a recent British randomized trial comparing SEMS vs. plastic stents or other re-canalization interventions showed that patients treated with SEMSs may have worse QoL following the treatment and a shorter survival ( 3 ).…”
Section: Interventions (Consort 5)mentioning
confidence: 99%